Ownership structure and corporate tax aggressiveness: A conceptual approach - Salihu, Ibrahim Aramide; Annuar, Hairul Azlan; Sheikh Obid, Siti Normala (2013)
Purpose – This paper proposes a conceptual framework for the study of the determinants of corporate tax aggressiveness in a concentrated ownership setting with an emerging capital market. Design/methodology/approach – The paper uses the theoretical approach in identifying the potential benefits and costs of corporate tax aggressiveness to develop a framework of the likely forms of ownership that could be related more to tax aggressive planning. Findings – Three forms of corporate ownership are proposed as potential determinants of corporate tax aggressiveness given the costs/benefits consideration of the aggressive activities and the findings from related studies. These are family, government and foreign ownerships. Research limitations/implications – While the present study is conceptual in nature, the developed framework could provide a basis for further empirical enquiries. Practical implication - The findings from the further empirical investigations will be a useful guide to the selection of corporate tax audit cases for effective and efficient tax administration. Originality/value – The study is among the very few studies on corporate tax aggressiveness, especially from emerging economies. The developed framework is also unique given the nature of the corporate ownership obtainable in the context of the study.